Morfologia, morfometria, distribuição de células mucosas e de cloreto em embriões e larvas de jundiá, Rhamdia quelen (Heptapteridae). Efeito do pH e concentração de cálcio e magnésio da água - Silva, Lenise Vargas Flôres da (Universidade Federal de São Carlos, 2006)
The ions Ca2+, Mg2+ and the water pH influence the morphological and morphometric characters and also in the ionic regulation of fish. The objective of this study was describe the morphological and morphometric development pattern of Rhamdia quelen embryo and larvae; and to identify and determine the distribution of mucous and chloride cells in order to evaluate the effect of water pH and hardness in different Ca2+ and Mg2+ concentration. After fertilization the eggs were maintained at water pH 7.0 and 8.0 with three different Ca2+: Mg2+ concentrations (mg L-1): hardness 20 mg L-1 CaCO3 (5.0 Ca2+: 2.08 Mg2+, control) and hardness 70 mg L-1 CaCO3 (20 Ca2+:5.59 Mg2+ and 23 Ca2+: 2.08 Mg2+) at 24±1oC. The eggs (24 h post fertilization- hpf) and larvae (each 6 hours) 6 to 48 and 216 h post hatchery (hph) were collected to analyze the hatching rate, survival and larvae growth, morphological and morphometrics characters associates the vision (eye), feeding (development and functionality digestive tract) and swimming abilities (fins), the distribution of mucus and chloride cells, Na+/K+-ATPase activity enzyme, and whole body ionic content in embryo and larvae homogenate. The fertilization, hatching rate, post-hatch survival, weight and length (48 and 216h) were higher in pH 8,0 and did not show significance difference related with Ca2+: Mg2+ concentrations. These suggest that the pH 8.0 is indicated to Rhamdia quelen larvae culture. The increase of water hardness to 70 mg L-1 CaCO3, mainly 20 mg L-1 Ca2+ and 5,59 mg L-1 Mg2+ concentrations is recommended to both pH device improve the total body area larvae. The increase of hardness with 23 mg L-1 Ca2+, is not adequate for Rhamdia quelen larvae, as this Ca2+ concentration occurs an ionic unbalance Na+ and Cl- in both pHs. However, the morphology did not change by pH and Ca2+: Mg2+ concentrations used. The developmental stage between 6-216 hph was considered as critic period, device the development of osmorregulatory structures (gills, intestine and kidney) and the necessary changes to begin the exogenous feeding (open mouth, digestive tract, urogenital hole). Therefore, it is important information to researches and/or fisheries to improve the techniques and handlings for Rhamdia quelen early stages larvae culture to optimize the environmental conditions. The mucous cell density show a relation with water Ca2+ concentration, and it is suggest that beyond the possible adaptive responses, apparently the mucous cells number in silver catfish larvae (Rhamdia quelen) are influenced by hardness (Ca2+ increases) and water pH in the early phases. The larvae cultivated in pH 7.0 show high mucous cell and chloride cell number than in pH 8.0. The water hardness 70 mg L-1 CaCO3 (independently Ca2+ and Mg2+ concentration) changed the chloride cell density in the first hours post hatchery (6-12 h), and the number of these cells was lower in both pHs. Then, these results suggest that the mucous and chloride cell number can be modulated by ionic environmental condition in the early develpment of silver catfish larvae after hatchery. The thesis was organized in chapters, a general introduction and the objectives, and it was followed by chapter 1 about morphology and morphometry of embryo and larvae, chapter 2 about the distribution of mucous cells and chapter 3 about the distribution the chloride cells of silver catfish (Rhamdia quelen) embryo and it was with an integrated synthesis of study, the general conclusions and finish considerations.
Keywords: Teleosteos; Rhamdia quelen; Células - cloreto; Células - mucosas; Peixe-larva; CIENCIAS BIOLOGICAS::ECOLOGIA